Utilizing Foreignization and Domestication Strategies in Religious Translation and Their Impact on Meaning Interpretation of the Translated Texts: With Special Reference to Surah Al-Waqi’ah in English translation - Khan, Mohammad Imran (International Journal of Language and Literary Studies, 2025)
This paper explores the use of foreignization and domestication strategies in English translation of religious texts more specifically the Surah Al-Waqi’ah in the Quran as the subject in the analysis. Based on translation theory and hermeneutics, the study examines the effect of strategic choices on the clarity of the theological message, cultural point of connection and the interpretation of the reader. Based on comparative text analysis between three major English versions Yusuf Ali, Saheeh International, and Pickthall, the study maintains that foreignization and domestication are mutually determining factors to preservation of doctrine and local flavour, and accessibility and emotional resonance respectively. The results outline the moral as well as interpretive conflicts of the religious translation and propose multi-contextual approach based on the necessity to compromise between adherence to holy meaning and attentiveness to multimedia audiences. Conclusions are presented concerning implications to translators, teachers and scholars and conceived in the role of the translator being a linguistic interpreter but also a theological one.